Didyma, Türkei. Site Management und Tempelkonsolidierung. Die Arbeiten der Jahre 2017 und 2018 - von Gaisberg, Elgin; Bumke, Helga (e-Forschungsberichte des DAI, 2019)
The Site Management Project, which based on a concept developed in 2012/2013, pursues two main objectives: to provide visitors access to the excavation area of the Sacred Way, and to establish a connection with the separated area of the Apollo Temple by means of a new visitor guidance system. As in previous years consolidation work on the Apollo Temple has been done in accordance with international standards. The completion of the examination of the temple but also a mapping of the damages and consolidation work already undertaken since 1992 constituted additional measures in 2018. Another task was to determine and to visualize all the rebuilt parts, carried out during the excavation of the temple at the beginning of the 20th century.